Reviewing the Traditional/Modern Uses, Phytochemistry, Essential Oils/Extracts and Pharmacology of Embelia ribes Burm. - Vineet Sharma; Dev Nath Singh Gautam; Andrei-Flavius Radu; Tapan Behl; Simona Gabriela Bungau; Cosmin Mihai Vesa (MDPI AG, 2022)
Objectives: Embelia ribes Burm. (E. ribes, Myrsinaceae), also known as Vidanga in Ayurveda, has been shown to have significant therapeutic benefits on several disorders, and its main chemical bioactive constituent, embelin, has the therapeutic potential to be converted into innovative drugs, which is why it has recently received considerable interest. In the present work, we provide a higher level of comprehension, awareness, and extensive knowledge of the traditional uses, phytochemistry, and pharmacological characteristics of E. ribes throughout the last several decades (February 1965 to June 2021), emphasizing the importance of the study of essential oils extracted from E. ribes, which show a major potential for exerting antioxidant and anti-inflammatory activity. Materials and Methods: Google Scholar, MEDLINE, EMBASE, Scifinder, Scopus, and ScienceDirect were used to conduct a thorough literature search. Results: E. ribes is high in essential oils, alkaloids, flavonoids, steroids, and phenolics, all of which have medicinal benefits. The essential oils/extracts and isolated chemical constituents exhibited antioxidant activity, wound healing, antidiabetic, central nervous system (CNS)-related disease, antiviral, antiobesity, cardioprotective, antifungal, antibacterial, and antifertility activity, among other promising pharmacological effects. Conclusion: The translation between traditional applications and modern medicine may make E. ribes a promising target for the implementation of innovative medication. To investigate the efficacy and safety profile of E. ribes, further high-quality preclinical studies using advanced methodologies are required.